PENERAPAN TEORI BRUNER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 13 PEKANBARU - Sunika Arista; Gustimal Witri; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to improve student learning outcomes through the application of Bruner's theory. This type of research is Collaborative Classroom Action Research (CAR). Which consists of 4 stages in each cycle. Namely planning, implementation, observation and reflection. This study was conducted in 2 cycles. This research was carried out in SD Negeri 13 Pekanbaru class III with a total of 22 students. Based on the results of the study, the results of observations of teacher activities in the first cycle of the meeting 1 percentage was 65.62% with enough categories increasing to 78.12% with good categories at meeting 2, increasing again in the second cycle of meeting 2 with a percentage of 84.37% with categories still good then increased to 90.62% with a very good category. While the activity of students in the first cycle of the meeting 1 percentage was 59.37% with enough categories increasing to 75.00 in the second meeting with good categories, then increasing in the second cycle of meetings 1 percentage 84.37% with good categories and increasing again at meeting 2 93.75% with a very good category. Based on the data analysis, the average student learning outcomes have increased, namely at the average value on the base score 66.81 increased to 73.18 in the first cycle with an increase of 10.89%, increasing again in the second cycle, the average value is 85 , 00 with an increase of 27.22%. This shows that the Application of Bruner Theory can Improve Mathematics Learning Outcomes of Class III Students of SD Negeri 13 Pekanbaru.Key Words: Bruner Theory, Mathematics Learning Outcomes